THE EFFECT OF EMPLOYEE ENGAGEMENT AND WORKLOAD ON EMPLOYEE PERFORMANCE MEDIATED BY EMPLOYEE WORK SATISFACTION IN THE ADMINISTRATION SECTION OF THE AIRPORT AUTHORITY REGION II OFFICE MEDAN - Egarius Budiarto; Sri Rahayu; Wilchan Robain (Lafadz Jaya Publisher, 2023)
The purpose of this study was to determine and analyze the effect of Employee Engagement and Workload on Employee Performance which is mediated by Employee Job Satisfaction. This type of research is associative quantitative. The location of this research is the Airport Authority Region II Medan. The population and sample in this study were 70 employees (saturated sample). This research model uses Path analysis, and the measurement tool uses Smart PLS 3.3.3. Data collection was carried out using a questionnaire. The results of the research are as follows: Workload has a positive and significant effect on employee satisfaction. Workload has no significant positive effect on employee performance. Employee Engagement has a positive and significant effect on Employee Satisfaction. Employee Engagement has a negative and insignificant effect on Employee Performance. Job Satisfaction has a positive and significant effect on Employee Performance. Workload has a positive and significant effect on Employee Performance through Job Satisfaction. Employee Engagement has a positive and significant effect on Employee Performance through Employee Satisfaction.